Lineages of Silene nutans developed rapid, strong, asymmetric postzygotic reproductive isolation in allopatry. (1st June 2017) - Martin, Hélène; Touzet, Pascal; Dufay, Mathilde; Godé, Cécile; Schmitt, Eric; Lahiani, Emna; Delph, Lynda F.; Van Rossum, Fabienne
Abstract: Reproductive isolation can rise either as a consequence of genomic divergence in allopatry or as a byproduct of divergent selection in parapatry. To determine whether reproductive isolation in gynodioecious Silene nutans results from allopatric divergence or from ecological adaptation following secondary contact, we investigated the pattern of postzygotic reproductive isolation and hybridization in natural populations using two phylogeographic lineages, western (W1) and eastern (E1). Experimental crosses between the lineages identified strong, asymmetric postzygotic isolation between the W1 and the E1 lineages, independent of geographic overlap. The proportion of ovules fertilized, seeds aborted, and seeds germinated revealed relatively little effect on the fitness of hybrids. In contrast, hybrid mortality was high and asymmetric: while half of the hybrid seedlings with western lineage mothers died, nearly all hybrid seedlings with E1 mothers died. This asymmetric mortality mirrored the proportion of chlorotic seedlings, and is congruent with cytonuclear incompatibility. We found no evidence of hybridization between the lineages in regions of co‐occurrence using nuclear and plastid markers. Together, our results are consistent with the hypothesis that strong postzygotic reproductive isolation involving cytonuclear incompatibilities arose in allopatry. We argue that the dynamics of cytonuclear gynodioecy could facilitate the evolution of reproductive isolation.